ACCELERATE and European Medicine Agency Paediatric Strategy Forum for medicinal product development for mature B-cell malignancies in children. (March 2019) - Pearson, Andrew D.J.; Scobie, Nicole; Norga, Koenraad; Ligas, Franca; Chiodin, Davy; Burke, Amos; Minard-Colin, Veronique; Adamson, Peter; Marshall, Lynley V.; Balakumaran, Arun; Benettaib, Bouchra; Bhargava, Pankaj; et al.
Abstract: Paediatric Strategy Forums have been created by the multistakeholder organisation, ACCELERATE, and the European Medicines Agency to facilitate dialogue between all relevant stakeholders and suggest strategies in critical areas of paediatric oncology drug development. As there are many medicines being developed for B-cell malignancies in adults but comparatively few in children with these malignancies, a Paediatric Strategy Forum was held to discuss the best approach to develop these products for children. It was concluded that as current frontline therapy is highly successful, despite associated acute toxicity, de-escalation of this or substitution of presently used drugs with new medicines can only be undertaken when there is an effective salvage regimen, which is currently not available. Therefore priority should be given to developing treatment for patients with relapsed and refractory mature B-cell lymphomas. The consensus of the clinicians attending the meeting was that CAR T-cells, T-cell engagers and antibody drug conjugates (excluding those with a vinca alkaloid–like drug) presently have the greatest probability of providing benefit in relapse in view of their mechanism of action. However, as producing autologous CAR T-cells currently takes at least 4 weeks, they are not products which could be quickly employed initially at relapse in rapidly progressing mature B-cell malignancies but only for the consolidation phase of the treatment. Global, industry-supported, academic-sponsored studies testing compounds from different pharmaceutical companies simultaneously should be considered in rare populations, and it was proposed that an international working group be formed to develop an overarching clinical trials strategy for these disease groups. Future Forums are planned for other relevant paediatric oncologic diseases with a high unmet medical need and relevant molecular targets. Highlights: Paediatric Strategy Forums involve all stakeholders in paediatric oncology drug development. There are many medicines being developed for B-cell malignancies in adults. However there are comparatively few in children with these malignancies. The priority is to develop therapy for relapsed/refractory mature B-cell lymphomas. CAR T-cells, T-cell engagers and antibody drug conjugates are the most promising agents.